Where stuff comes from : how toasters, toilets, cars, computers, and many others things come to be as they are - Molotch, Harvey Luskin (Routledge, 2003)
A sparkling tour of how things are created: the everyday objects of our life - paper clips, Post-its, bathtubs, cars and all the other stuff - are a delicate and clever intermingling of design, timing and functionality that mirrors contemporary life.